(untitled) (International Journal of Food and Nutritional Sciences, 2021)
Medicinal plants are rich sources of phytochemicals, forming the basis for traditional and modern medicine. Natural antioxidants from plants, such as flavonoids, tannins, and vitamins C & E, help counteract oxidative stress, which is linked to various diseases, including cancer and neurodegenerative disorders. Clematis heynei and Solanum virginianum is also produced beneficial effects in complications of the diabetes mellitus and obesity. Clematis heynei and Solanum virginianum are used for streptozotocin nicotinamide-induced diabetic rats. These plants produces dose-dependently antidiabetic activity. The Clematis heynei and Solanum virginianum has also seems have potent hypolipidemic activity, which lowers the cholesterol, triglyceride, total proteins and increasing high-density lipoproteins levels. The role of antioxidant activities of Clematis heynei and Solanum virginianum and active constituents play a role in preventing diabetic complications and antidiabetic activity of Clematis heynei and Solanum virginianum at 200 mg/kg of the dose was found to be more effective than 100 mg/kg of dose, its produced effects dose-dependently.